Rekonstruksi Manajemen Diklat Guru TIK di Lembaga Pendidikan Islam: Strategi Inovatif Menuju Profesionalisme Berkelanjutan di Era Society 5.0 - Hamidah, Asfiatul; Cahyanti, Nani Sri; Husain, Muhammad (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
This study aims to reconstruct the management of education and training (diklat) for Information and Communication Technology (ICT) teachers in Islamic educational institutions by designing innovative strategies that enhance sustainable professionalism in the Society 5.0 era. The study is motivated by the limited readiness of ICT teachers to master digital pedagogy and smart technology due to inadequate training systems. Using a qualitative approach with a case study method at SMK King Abdul Aziz, data were collected through participatory observation, in-depth interviews with principals, ICT teachers, and students, as well as documentation analysis. The data were analyzed using Miles and Huberman's interactive model. The findings reveal that current training programs remain top-down, lack contextual relevance, are not aligned with teachers' needs, and insufficiently integrate smart technologies or professional learning communities. This study contributes theoretically to the development of innovation-based training management models and offers practical guidance for Islamic schools and policymakers to build more responsive and transformative professional development systems.